The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.jcrs.2011.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Results of laser in situ keratomileusis performed using solid-state laser technology

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…[1][2][3][4][5] In experimental studies, solid-state lasers have shown no induction of thermal damage or adverse effects in deep corneal layers after photorefractive keratectomy. [1][2][3][4][5] In experimental studies, solid-state lasers have shown no induction of thermal damage or adverse effects in deep corneal layers after photorefractive keratectomy.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] In experimental studies, solid-state lasers have shown no induction of thermal damage or adverse effects in deep corneal layers after photorefractive keratectomy. [1][2][3][4][5] In experimental studies, solid-state lasers have shown no induction of thermal damage or adverse effects in deep corneal layers after photorefractive keratectomy.…”
mentioning
confidence: 99%
“…The gas-free lasers require less maintenance, with a relative reduction in costs due to the argon gas management, and the diode pump system is characterized by long-lasting effectiveness. The literature related to solid-state lasers comprises both experimental and clinical studies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In the studies on murine corneas, Ren et al and Tsiklis et al demonstrated similar histopathologic responses to solid-state laser and excimer laser ablations in murine corneas [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of clinical studies report results of refractive surgery performed with two solid-state lasers [ 2 , 8 , 9 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 ]. The LaserSoft (Katana Technologies, Kleinmachow, Germany), which operates at a 210 nm wavelength, 0.2 mm diameter Gaussian spot, and repetition rate of 2 kHz, and the Pulzar Z1 (Customvis, Perth, Australia), working with a 213 nm laser and a 0.6 mm spot with a repetition rate of 300 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 This technology has become an alternative in corneal refractive surgery, with some potential advantages over excimer lasers. There are few reports 22 of the outcomes of the use of solid state 213 nm lasers for refractive correction. The visual outcomes in our cohort were excellent with a significant improvement in logMAR UDVA and maintenance of logMAR CDVA.…”
Section: Discussionmentioning
confidence: 99%